Assessing HIV-1 subtype C infection dynamics, therapeutic responses and reservoir distribution using a humanized mouse model - Kaginkar, Snehal; Remling-Mulder, Leila; Sahoo, Ashashree; Pandey, Tejaswini; Gurav, Pranay; Sutar, Jyoti; Singh, Amit Kumar; Barnett, Ella; Panickan, Sivasankar; Akkina, Ramesh; Patel, Vainav (Frontiers in Immunology, 2025)
IntroductionWhile HIV-1 subtype C (HIV-1C) is the most prevalent and widely distributed subtype in the HIV pandemic, nearly all current prevention and therapeutic strategies are based on work with the subtype B (HIV-1B). HIV-1C displays distinct genetic and pathogenic features from that of HIV-1B. Thus, treatment approaches developed for HIV-1B need to be suitably optimized for HIV-1C. A suitable animal model will help delineate comparative aspects of HIV-1C and HIV-1B infections.MethodsHere, we used a humanized mouse model to evaluate HIV-1C infection, disease progression, response to anti-retroviral therapy (ART) and viral rebound following therapy interruption. A limited comparative study with a prototypical subtype B virus was also performed. Viral infection, immune cell dynamics, acquisition of anti-retroviral therapy (ART) resistance and anatomical reservoir distribution following extended and interrupted therapy were compared. ResultsIn comparison, lower early plasma viremia was observed with HIV-1C, but with similar rate of CD4+ T cell depletion as that of HIV-1B. Viral suppression by ART was delayed in the HIV-1C infected group with evidence, in one case, of acquired class wide resistance to integrase inhibitors, a critical component of current global therapy regimens. Also, HIV-1C infected animals displayed faster rebound viremia following ART interruption (ATI). Disparate patterns of tissue proviral DNA distribution were observed following extended ART and ATI suggestive of distinct sources of viral rebound. DiscussionIn this preliminary study, discernible differences were noted between HIV-1C and B with implications for prevention, therapeutics and curative strategies. Results from here also highlight the utility of the hu-HSC mouse model for future expanded studies in this context.